7 - Social Sciences and Policy Making in Africa: A Critical Review: by Sadig Rasheed - Sadig Rasheed (Africa Development, 1994)
A number of social scientists and organizations have, over the years, reflected on the evolution and problems of the social sciences (Mkandawire 1989; Ake 1983; Oyugi 1989; Katorobo 1985; Jitiadu 1985; Amin et al 1978) and the relationship between the social sciences and development in Africa.2 However, the need for an appropriate understanding of the relation ship between social sciences and policy making in Africa and the prevailing crisis in the state of this relationship make it more urgent than ever before that the social science community in Africa should reflect collectively, in a more systematic and critical manner, on this particular problématique and on its ramifications and future implications. This paper is intended to stimulate the debate within the aforementioned frame by providing an assessment of the state of the interface between social science and policy making in Africa and offering some perspectives on how this relationship should be perceived, evolve and be deliberately changed in the 1990s and beyond.